Conjugated Polymers: Low‐Dimensional Conduction Mechanisms in Highly Conductive and Transparent Conjugated Polymers (Adv. Mater. 31/2015). (13th August 2015) - Ugur, Asli; Katmis, Ferhat; Li, Mingda; Wu, Lijun; Zhu, Yimei; Varanasi, Kripa K.; Gleason, Karen K.
<x xml:space="preserve">Abstract</x> Optimal device performance for high‐end technologies requires a fundamental grasp of the transport properties at the nanoscale. In work by K. K. Varanasi, K. K. Gleason, and co‐workers on page 4604, a completely new aspect and understanding of the conduction mechanism of conducting polymers is introduced, allowing the applicability of the materials to be optimized. The electron conduction is diminished in thicker films due to the 3D nature of the conduction pathways. Conversely, in ultrathin layers having a 2D nature, the hopping mechanism is amplified, leading to ultraconductive and highly transparent thin films, which are crucial for technological applications.